2018
DOI: 10.1111/apha.13158
|View full text |Cite
|
Sign up to set email alerts
|

Muscle PGC‐1α in exercise and fasting‐induced regulation of hepatic UPR in mice

Abstract: This study provides for the first time evidence for transient pathway-specific activation of hepatic UPR and increase in markers of autophagy in the liver with acute exercise. On the other hand, fasting both increased and decreased UPR branches and seemed to increase autophagy. In addition, muscle PGC-1α seemed to dampen some of these responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In muscle cells, the UPR can be induced by metabolic factors (e.g., fatty acid) and exercise-related factors (e.g., PGC-1α) (Woodworth-Hobbs et al, 2017; Kristensen et al, 2018). Recent studies identified UPR markers in regenerating fibers of chronic myositis muscles (Vattemi et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In muscle cells, the UPR can be induced by metabolic factors (e.g., fatty acid) and exercise-related factors (e.g., PGC-1α) (Woodworth-Hobbs et al, 2017; Kristensen et al, 2018). Recent studies identified UPR markers in regenerating fibers of chronic myositis muscles (Vattemi et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Our recent work (Ding et al, 2018), with data described by others (Nagaraju, 2001; Wiendl et al, 2005), supports the intrinsic immune properties of muscle cells in inflammatory conditions. Despite the description of ER stress in the response to muscle metabolic consequences, acute stressors, and cancer cachexia (Bohnert et al, 2016, 2019; Woodworth-Hobbs et al, 2017; Kristensen et al, 2018), including autoimmune and genetic muscle disorders (Afroze and Kumar, 2017), the role of the individual arms of the UPR in regulating muscle fiber immune function has not been fully explained. Our results with CTX-treated mice provide evidence that the eIF2α and IRE1α arms of the UPR are critical for muscle fiber function during skeletal muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 h time point was chosen based on the previous findings that UPR markers were regulated at this time point (Kristensen et al . ). Exercise trained mice performed the last exercise bout 24 h prior to euthanization to prevent acute effects of exercise.…”
Section: Methodsmentioning
confidence: 97%
“…Elevated hepatic LC3II/I ratio, but not SQSTM1, was observed immediately after exercise in both WT and skeletal muscle-specific PGC1α overexpressing mice, a response that returned to baseline 2 h postexercise in both groups (52). Similarly, liver-specific PGC1αKO and WT mice also displayed an increased hepatic LC3II/I ratio after exercise (53).…”
Section: Effects Of Endurance Exercise On Liver Autophagymentioning
confidence: 99%